Evaluation of Bifenthrin and Acorus calamus Linn. Extract against Aedes aegypti L. and Aedes albopictus (Skuse) - S Sulaiman; DSF Abang Kamarudin; H Othman (Tehran University of Medical Sciences, 2008)
Background: Bifenthrin and Acorus calamus Linn extract were evaluated against dengue vectors in the laboratory. Methods: Both Bifenthrin and Acorus calamus Linn crude hexane extract were bioassayed against the adults and larval stages of dengue vectors Aedes aegypti L. and Aedes albopictus(Skuse) in the laboratory. Results: The A. calamus crude hexane extract exhibited a larvicidal activity against 4th-instar Ae. aegypti larvae with LC50 and LC90 values of 0.4418 and 11.3935 ppm respectively. The plant crude extract exhibited against Ae. albopictus larvae with a higher LC50 and LC90 values of 21.2555 ppm and 36.1061 ppm, respectively. There was a significant difference on the effect of A. calamus extract on both Aedes spp. Larvae (P< 0.05). However, bifenthrin showed a significant difference on larvicidal effect to that of A. calamus hexane extract on both Aedes spp (P< 0.05). In testing the adulticidal activity, this plant extract exhibited the LC50 and LC90 values of 17.4075 and 252.9458 ppm against Ae .aegypti and a higher LC50 and LC90 values of 43.9952 and 446.1365 ppm respectively on Ae. albopictus. There was no significant difference on the effect of A. calamus extract on both Aedes spp adults (P> 0.05). Conclusion: Bifenthrin however showed a significant difference on both Aedes spp adults (P< 0.05). With the wide availability of A. calamus in Malaysia, it could be utilized for controlling dengue vectors.